Timing of postoperative weightbearing in the treatment of traumatic chondral injuries of the knee in athletes - A systematic review of current concepts in clinical practice - Sarah Rolf; Cheuk-Kin Kwan; Martin Stoddart; Yan Li; Sai-Chuen Fu (Elsevier, 2022)
Background: Surgery aims to stimulate healing and enable a safe return to sport in athletes with symptomatic cartilage lesions of the knee. Timing of postoperative weightbearing is crucial, balancing a stimulation of the healing and avoiding reinjury.To explore current concepts of timing to partial and full weightbearing and rate of return to sport in athletes after articular cartilage surgery of the knee.Systematic Review of studies with level of evidence I-III Methods: Four databases (Pubmed, Web of Science, Scopus and Embase) were searched using a predetermined keyword strategy. Two independent reviewers screened results according to inclusion and exclusion criteria. Modified Coleman Methodology Score (mCMS) was used for the quality assessment. Results: 5294 records were found. Data from ten studies was extracted after duplicate removal, title and abstract screening and full-text evaluation. Eight of the ten studies included a detailed rehabilitation protocol, including 336 out of a total athletic population of 401. 62% began partial weightbearing (PWB) 1-2 weeks postoperatively, while 38% began within 3-4 weeks. The studies that had a later PWB all returned to full weightbearing (FWB) within 6-8 weeks. One study with early PWB returned to early FWB, while the other two returned 10-12 weeks postoperatively. "Return to Sport" (RTS) was the most common reported outcome measure, with most studies reporting RTS at 80% or higher. Conclusion: There is no clear evidence that the timing of weightbearing (WB) affects the outcome and return to sport in athletes after surgery for focal full-thickness cartilage lesions of the knee. On the other hand, there seems to be no adverse effects in adopting an early WB strategy, currently defined differently by different authors. Further studies directly comparing the timing of WB for specific surgical procedures in athletes and with relevant control groups is recommended. There is a need for a consensus in regard to more exactly defining "early" vs "late" weightbearing in relation to a universal and precisely defined state of healing.